Oxidation of cinnamyl alcohol using bimetallic Au–Pd/TiO2 catalysts: a deactivation study in a continuous flow packed bed microreactor - Wu, Gaowei; Brett, Gemma L.; Cao, Enhong; Constantinou, Achilleas; Ellis, Peter; Kuhn, Simon; Hutchings, Graham J.; Bethell, Donald; Gavriilidis, Asterios (My University, 2016)
The stability of a bimetallic Au-Pd/TiO2 catalyst was examined in a packed bed microreactor for the oxidation of cinnamyl alcohol dissolved in toluene. The catalyst was prepared by co-impregnation with a Au-Pd weight ratio of 1:19. Experiments were performed at 80-120 °C, oxygen concentration 0-100% and total pressure 4 bara. Principal products observed were cinnamaldehyde, 3-phenyl-1-propanol and trans-β-methylstyrene. Although the same catalyst was shown to possess good stability in the oxidation of benzyl alcohol, it deactivated during the oxidation of cinnamyl alcohol, particularly at elevated reaction temperatures. Higher concentration of oxygen used for the reaction led to improved cinnamaldehyde selectivity but lower conversion and higher deactivation rates. Treatment with hydrogen recovered only a fraction of the activity. Deactivation was attributed to Pd leaching and a complex effect of oxygen.
Keywords: Catalysts; Chemical reactors; Gold alloys; Oxidation; Oxygen; Packed beds; Reaction rates